GROWTH AND YIELD OF Eucalyptus grandis HILL EX MAIDEN AT AEK NAULI SIMALUNGUN NORTH SUMATRA - Aswandi Aswandi (Pusbindiklat - LIPI, 2011)
Sustainable forest management need an effective yield regulation. This is depend on precision of growth and yield prediction on determination of rotation, harvesting intensity, thinning regime and another silviculture option. The objective of the study was to develop growth and yield model and deﬁ ned optimum cutting rotation for Eucalyptus grandis Hill ex Maiden timber estate at Aek Nauli Simalungun North Sumatra. Current growth estimation and yield prediction models were studied using data from 15 permanent sampling plots. Data from annual measurement were used to formulate the models which include stand diameter and height function, basal area and stand volume function. Site quality was calculated using site index equation SI = H*(1+10.03*e)/(1+10.03*e. This equation was developed based on relationship dominant height with stand age. Site index in that region have varies from 18.99 to 35.26. According on interception of curva Current Annual Increment (CAI) and Mean Annual Increment (MAI) were deﬁ ned optimum cutting rotation at 6 year. Volume yield at this end rotation is 165,24 m -0.59*1/83/hawith MAI (Mean Annual Increment) 27,54 m /ha/yr. Yield prediction model were developed by regression analysis. The optimum of equations of mean of diameter, height, basal area and stand volume showed as follow: a. Stand dbh model : ln D = 0.743 + 0.363 ln A + 0.142 lnS + 0.313 ln B; b. Stand mean height model: lnH = - 0.206 + 0.247 lnA + 0.100 lnB + 0.822 lnS; c. Volume yield model : ln V = - 1.96 + 0.526 ln A + 0.548ln B + 1.38 ln S. Where D : dbh (cm), H: mean height (h), V : stand volume (m33 ha), A : age (yr), B: basal area (m), and S : site index. 2-1-0.59A",